Game of Chance : The Royal - Book 2 - Stoker, Susan (Seattle : Montlake, 2023)
"Former military man and member of a royal family Callum Redmon can't deny his sense of responsibility. So when his cousin's latest love interest claims to have a stalker, Cal reluctantly meets with the young woman and her mother. He wants to write off the situation as a complete farce--if only his feelings for another member of the household could be as easily dismissed. Since her father's death seventeen years ago, Juniper Rose has been at the cruel beck and call of her stepmother and stepsister. Her fantasies of escape mean leaving behind her father's beloved home, but enough is enough: when Cal offers her a way out sooner rather than later, June takes the leap. Cal's home in Maine with his military brothers seems like the safest place to start fresh. But as Cal and June's fairy-tale romance blossoms into something real, they find that the dangers stalking them may have been real all along"--
Keywords: Man-woman relationships -- Fiction; Veterans -- Fiction; Nobility -- Fiction; Stepfamilies -- Fiction; Stalking -- Fiction; Maine -- Fiction; Romantic suspense novels; Romance fiction